1993
DOI: 10.1136/bmj.307.6910.988
|View full text |Cite
|
Sign up to set email alerts
|

Adverse reactions to influenza vaccine in elderly people: randomised double blind placebo controlled trial.

Abstract: Objective-To assess the frequency and type of side effects after influenza vaccination in elderly people.Design-Randomised double blind placebo controlled study.Setting-15 general practices in the southern Netherlands.Subjects-1806 patients aged 60 or older, of whom 904 received influenza vaccine and 902 placebo.Main outcome measures-Adverse reactions reported on postal questionnaire completed four weeks after vaccination.Results-210 (23%) patients given vaccine reported one or more adverse reactions compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
76
0
5

Year Published

1996
1996
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(93 citation statements)
references
References 14 publications
11
76
0
5
Order By: Relevance
“…Systemic symptoms or disability are seen as often in persons receiving placebo as in those who have received inactivated influenza vaccine. Mild local reactions, such as a ''sore arm'', are less common after placebo than after active substance, 5-10% versus 15-20%, respectively [265][266][267]. The inactivated vaccine is also safe to administer to patients with asthma, including those with severe asthma [268].…”
Section: Prevention By Vaccinationmentioning
confidence: 99%
“…Systemic symptoms or disability are seen as often in persons receiving placebo as in those who have received inactivated influenza vaccine. Mild local reactions, such as a ''sore arm'', are less common after placebo than after active substance, 5-10% versus 15-20%, respectively [265][266][267]. The inactivated vaccine is also safe to administer to patients with asthma, including those with severe asthma [268].…”
Section: Prevention By Vaccinationmentioning
confidence: 99%
“…In a randomized, double-blind, crossover trial in the elderly, Margolis and colleagues 57 reported no significant systemic symptoms. In another randomized clinical trial, Govaert et al 58 found no increase in systemic adverse reactions, only an increase in local side effects.…”
Section: Potential Adverse Effectsmentioning
confidence: 91%
“…F > M. Govaert et al 43 1,806 responded to questionnaire; 16 non-responders in each group, 904 vaccine, 902 placebo.…”
Section: F > M and Tetanus-diphtheria (Td)mentioning
confidence: 99%